Ukraine energy policy review 2006 (OECD/IEA, 2006)
Ukraine has one of the most energy-intensive economies in the industrialized world. While energy consumption has dropped since the country's independence, reliance on imports, particularly on gas from Russia, has not declined. This dependence increases risks for security of supply. As tension between Ukraine and its main energy supplier has grown in recent years, the country's energy policy is driven by a strong desire to improve domestic energy security and reduce natural gas imports. Energy transit through Ukraine is significant. Due to its geographic position, the country plays a major role in securing Europe's energy needs: 84% of Russian gas supplies to Europe transit through Ukraine via pipeline. How can the country meet these challenges? This book identifies three key priority areas for action: energy efficiency, cost-reflective pricing and transparency. Efficiency represents not only Ukraine's single best opportunity to improve energy security but is also vital for the country's growth and development. The review covers all aspects of the energy sector, such as energy demand, the policy framework and subsectors.--Publisher summary.